2018
DOI: 10.1016/j.physleta.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical analysis of bounded and unbounded orbits in a generalized Hénon–Heiles system

Abstract: The Hénon-Heiles potential was first proposed as a simplified version of the gravitational potential experimented by a star in the presence of a galactic center. Currently, this system is considered a paradigm in dynamical systems because despite its simplicity exhibits a very complex dynamical behavior. In the present paper, we perform a series expansion up to the fifth-order of a potential with axial and reflection symmetries, which after some transformations, leads to a generalized Hénon-Heiles potential. S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
2
14
0
1
Order By: Relevance
“… Our findings are in agreement with previous studies related to the influence of perturbing terms in the dynamics of open and closed astrophysical systems [17,18,19].…”
Section: Discussionsupporting
confidence: 93%
“… Our findings are in agreement with previous studies related to the influence of perturbing terms in the dynamics of open and closed astrophysical systems [17,18,19].…”
Section: Discussionsupporting
confidence: 93%
“…Around 1980, Verhulst [10] expanded the potential (2) up to the fourth order seeking to study resonances 1 : 1, 1 : 2, 1 : 3, and 2 : 1. Some years ago, a generalized Hénon-Heiles potential was derived by expanding the effective potential up to the fifth order, aiming to study the equilibrium points and basins of convergence of the new potential [11] and to analyze the dynamical effect on bounded and unbounded orbits of including higher-order terms in the series expansion [12]. More recently, a seventhorder version of the stationary axisymmetric potential was presented [13], and it was found that when higher-order contributions of the potential are taken into account, the chaoticity of the system is reduced in comparison with the lower-order version of the Hénon-Heiles system.…”
Section: V(r Z) � U(r Z)mentioning
confidence: 99%
“…Potential (2) is derived as a Taylor expansion up to the 5-th order of a general potential with axial and reflection symmetries. More information about the exact expansion and the derivation of the generalized potential is given in [11].…”
Section: Properties Of the Dynamical Systemmentioning
confidence: 99%
“…The Hénon-Heiles Hamiltonian is a two-dimensional time-independent dynamical system, originally proposed as a simplified version of the gravitational potential experimented by a star orbiting around an axially symmetric galaxy (see e.g., [13]). An extension of this potential up to the fourth-order was performed by Verhulst [19], while in [11] we generalized the Hénon-Heiles potential up to the fifth-order. In the present paper, we examine the basins of convergence in the fifth-order generalization of the Hénon-Heiles Hamiltonian (in all that follows GHH).…”
Section: Introductionmentioning
confidence: 99%